The Effect of the kinds of ripening stimulant on the quality of Tamarillo - Efrida Yanti Anna P.; Elisa Julianti; Mimi Nurminah (Universitas Sumatera Utara, 2013)
The aim of this research was to find the effect of kinds of ripening stimulant and maturity stage on the quality of Tamarillo. This research had been performed using factorial completely randomized design with two factors, i.e maturity stage M1 = 70-80%, M2 = 85-90% , and kind of ripening stimulant P1 = Ethephon 750 ppm, P2 = Ethylene 250 ppm, P3 = Acetylene 250 ppm, P4 = Calcium Carbide 0,5%. Ripening was performed for 6 days at 28oC. Parameters analyzed were total soluble solid, acid content, maturity index, vitamin C content, weight lost, moisture content, hardness, color score, organoleptic values (color, aroma, texture) and concentration of carbon dioxide. The results showed that the maturity stage had highly significant effect on respiration rate, total slolube solid, acid content, hardness, color score, hedonic score of colors and texture. Kind of ripening stimulant had highly significant effect on concentration of carbon dioxide, moisture content, maturity index, color index, organoleptic values (color, smell, texture), and had significant effect on weight loss, vitamin C content. The interaction of maturity stage and kinds of ripening stimulant had highly significant effect on vitamin C content, marutity index, hardness, color index, and hedonic score of texture.